VOCs and PM listing of Eucalyptus globulus combustion in residential wood stoves - Henríquez, Francisco; Hernández, Diógenes; Varas-Concha, Felipe; Gutierrez, Camila; Quinteros-Lama, Héctor; Morales-Ferreiro, Jorge O. (Maderas. Ciencia y Tecnología, 2022)
Pollutant residential emissions from wood stoves have significant impacts both on the environment and people's health. The above makes it essential to know the types of volatile organic compounds emitted during combustion and explore their relationship with particulate matter and greenhouse gas emissions. This paper studies and analyzes these emissions using Eucalyptus globulus as fuel varying its moisture levels. Emissions were determined using an adapted commercial stove. The concentration levels of volatile organic compounds and particulate matter increase with the moisture of wood. When analyzing volatile organic compounds, particulate matter, and O2 with the combustion stages of wood, it is found that their concentrations were higher in the ignition and the reload stage. The concentrations of CO2 and NOx were higher in the reload stage. Other chemical compounds, such as toluene, xylene, and benzene, were also found within the volatile organic compounds listing, which increased their concentration in the ignition and stable reload stages. However, in the quenching stage, they are not present. Finally, the dispersion of these molecules in the environment is evaluated, obtaining that if the atmospheric conditions are adverse, these molecules remain in the environment in direct contact with the people living in those places.